A multicentre 'end to end' dosimetry audit of motion management (4DCT-defined motion envelope) in radiotherapy. Issue 3 (December 2017) - Palmer, Antony L.; Nash, David; Kearton, John R.; Jafari, Shakardokht M.; Muscat, Sarah
Abstract: Purpose: External dosimetry audit is valuable for the assurance of radiotherapy quality. However, motion management has not been rigorously audited, despite its complexity and importance for accuracy. We describe the first end-to-end dosimetry audit for non-SABR (stereotactic ablative body radiotherapy) lung treatments, measuring dose accumulation in a moving target, and assessing adequacy of target dose coverage. Materials and methods: A respiratory motion lung-phantom with custom-designed insert was used. Dose was measured with radiochromic film, employing triple-channel dosimetry and uncertainty reduction. The host's 4DCT scan, outlining and planning techniques were used. Measurements with the phantom static and then moving at treatment delivery separated inherent treatment uncertainties from motion effects. Calculated and measured dose distributions were compared by isodose overlay, gamma analysis, and we introduce the concept of 'dose plane histograms' for clinically relevant interpretation of film dosimetry. Results: 12 radiotherapy centres and 19 plans were audited: conformal, IMRT (intensity modulated radiotherapy) and VMAT (volumetric modulated radiotherapy). Excellent agreement between planned and static-phantom results were seen (mean gamma pass 98.7% at 3% 2 mm). Dose blurring was evident in the moving-phantom measurements (mean gamma pass 88.2% at 3% 2 mm). Planning techniques for motion management were adequate to deliver the intended moving-target dose coverage. Conclusions: A novel, clinically-relevant, end-to-end dosimetry audit of motion management strategies in radiotherapy is reported.